Assessment of Nasopharyngeal Cancer in Young Patients Aged ≤ 30 Years - Zhu, Yi; Song, Xinmao; Li, Ruichen; Quan, Huatao; Yan, Li (Frontiers in Oncology, 2019)
Purpose: This study assessed the prognosis of young patients with nasopharyngeal cancer (NPC), both domestic and foreign, using data from the Surveillance, Epidemiology and End Results (SEER) database, a population-based database, and departmental records. Methods: Patients diagnosed with NPC from 2004 to 2016 in the SEER database were reviewed. Young patients aged ≤30 years when diagnosed, were compared with older patients. The medical records of patients with NPC aged ≤30 years in our own department were also reviewed. The prognostic effects of different variables, including age, sex, race, tumor stage, pathology, radiation, and chemotherapy were assessed by Kaplan–Meier and Cox analyses. Results: A total of 212 foreign and 257 domestic patients, with mean ages of 21.5 and 22.9 years and median ages of 22 and 24 years, respectively, were included. In SEER database, younger NPC patients had a more advanced tumor stage (74.5% stage III/IV vs. 63.1% in older patients) and a worse pathological differentiation, but a better prognosis (P < 0.0001). Interestingly, the younger the patient, the better the prognosis. Younger patients received a higher proportion of chemotherapy. M stage, overall stage and radiation were the primary prognostic factors. Similar and more comprehensive results were found in our center. Patients with distant metastases, at a primary visit, had worse diagnoses. Intensity-modulated radiotherapy and three-dimensional conventional radiotherapy had minimal effects on survival in young patients in our center. Most patients from our department received chemotherapy, and different induction chemotherapy regimens resulted in similar survival prognoses. Conclusions: Young patients with NPC usually present at an advanced stage, but have a better overall prognosis. How to treat patients with metastasis is critical for improving prognoses in young NPC patients.